Pengembangan Media E-Comican pada Materi Sistem Gerak untuk Kelas 6 SDN Candi 01 Semarang - Erlina Nimastuti; Fine Reffiane; Asep Ardiyanto (SENTRI: Jurnal Riset Ilmiah, 2026)
This study aims to develop E-Comican learning media based on the Canva application for the human movement system material for sixth-grade students at SDN Candi 01 Semarang. This research employed a Research and Development (R&D) method using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects were 25 sixth-grade students of SDN Candi 01 Semarang. Data were collected through questionnaires, observations, interviews, and tests. The research instruments were used to determine the feasibility, practicality, and effectiveness of the media in improving students' learning outcomes. Data were analyzed using descriptive quantitative and qualitative methods. The results indicated that the Canva-based E-Comican learning media was feasible and practical for use in the learning process. Furthermore, the paired sample t-test results showed a significance value of 0.000 < 0.05, indicating a significant difference between pretest and posttest scores. Therefore, the Canva-based E-Comican learning media is effective in enhancing students' understanding of the human movement system material.